1996
DOI: 10.1002/actp.1996.010471103
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and polymerization of oxo‐crown ethers

Abstract: A novel synthetic route to and a polymerization procedure for 0x0-crown ethers 2,ll -dioxo-18-crown-6 (l), 2-0x0-12-crown-4(2) and 2-0x0-2 1-crown-7 (3) are described. Cyclization of the o-hydroxycarboxylic acid precursors of 1-3 has been achieved by heating these precursors in the presence of a Lewis acid catalyst (CoClZ) and a template salt (MCl). Cyclization yields up to 82% were reached, using CsCl as template salt. 0x0-crown ethers 1-3 have been polymerized using SnOctz as catalyst, giving polymers with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
3
13
0
Order By: Relevance
“…In agreement with earlier reports [24], we found that acids of this type tend to oligomerize on storage. For example acid 4 after storage for 14 days at 23°C had oligomerized to give, by high pressure liquid chromatography (HPLC) analysis and mass spectrometry (MS), a mixture of the starting acid (88%), the linear dimer (8%) and the linear trimer (2%).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…In agreement with earlier reports [24], we found that acids of this type tend to oligomerize on storage. For example acid 4 after storage for 14 days at 23°C had oligomerized to give, by high pressure liquid chromatography (HPLC) analysis and mass spectrometry (MS), a mixture of the starting acid (88%), the linear dimer (8%) and the linear trimer (2%).…”
Section: Resultssupporting
confidence: 94%
“…Hydroxy-acids 4 [24], 5 [24] and 6 [25] were prepared, respectively, from di-, tri-and tetra-ethylene glycol by literature methods. In agreement with earlier reports [24], we found that acids of this type tend to oligomerize on storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…O-Monobenzyl hexaethylene glycol has been described elsewhere. 22 Oligomer 5 was synthesized by protection of Omonobenzyl hexaethylene glycol with MEMCl in refluxing CH 2 Cl 2 , employing N(i-Pr) 2 Et as HCl scavenger. Production of the quinoline-derivatized oligomer (SS)-6 was achieved by tosylation of the R,ω-diol (SS)-8 in CH 2 -Cl 2 using KOH as base and by coupling of the resulting tosylate (SS)-9 with 8-hydroxyquinoline (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…The final cyclization step was achieved by heating the appropriate ω-hydroxycarboxylic acid precursor with the Lewis acid CoCl 2 (.11 mol %) at 250°C in a Kugelrohr apparatus. 12 An almost pure distillate could be collected, when reduced pressures of 2-3 and 8 mmHg were applied for (S)-21 and (S)-22, respectively. Chromatography afforded the 2-oxo-12-crown-4 compounds (S)-5 and (S)-6 in yields of 72% and 56%, respectively.…”
Section: Synthesis Of the Alkyl-modified Oxo-crown Ethers (Ss)-4 (S)mentioning
confidence: 99%